Perceived discrimination in middle-aged and older adults: Comparison between England and the United States - Amirova, Aliya; Rimes, Katharine A.; Hackett, Ruth A. (Frontiers in Public Health, 2022)
Objectives: This study examined differences in perceived discrimination across multiple characteristics in England and the United States (US), in middle- and older-aged adults. Methods: Using data from the English Longitudinal Study of Ageing (N = 8671) and the US-based Health and Retirement Study (N = 7927), we assessed cross-national differences in perceived discrimination attributed to disability, financial status, sex, race, sexual orientation, and weight. We also compared how perceived discrimination varied with socioeconomic position (SEP) based on wealth. Results: Perceived discrimination due to financial status was more common in England (6.65%) than in the US (2.14%) adjusting for age, sex, and wealth (Odds Ratio (OR) = 1.09, 95% CI [1.07; 1.10]). This affected people of low but not high SEP. Sexual orientation discrimination was more common in England (0.72% vs 0.15%, OR = 4.61, 95% CI [2.48; 8.57]). Sex-based perceived discrimination was more prevalent in the US (12.42%) than England (9.07%) adjusting for age and wealth (OR = 0.87, 95% CI [0.86; 0.89]). Cross-national differences in sex discrimination did not vary with SEP. Racism was the most common type of perceived discrimination reported in both samples (England: 17.84%, US: 19.80%), with no significant cross-national differences after adjustment for sex. Discussion: Perceived discrimination attributed to financial status and sexual orientation were more prevalent in England, while more women perceived sex discrimination in the US. This study suggests that country-specific and socioeconomic factors affect the prevalence of perceived discrimination. This may be relevant when targeting interventions aimed at reducing perceived discrimination.